2001
DOI: 10.1055/s-2001-15705
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologie und Kosten von Asthma bronchiale und chronischer Bronchitis in Deutschland

Abstract: The data suggest that therapeutic progress and cessation of smoking can provide distinctive savings of direct costs and even more of indirect costs of AB and CB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 3 publications
1
7
0
4
Order By: Relevance
“…Asthma therefore poses a significant burden of disease for the affected patients. The annual mean sick leave days in employed asthma patients are around 23 days [6]. In Germany the total direct costs of asthma were measured to be about 2.35 billion euro; the costs for sick leave days caused by asthma were estimated to be 242 million euro for the year 2006 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Asthma therefore poses a significant burden of disease for the affected patients. The annual mean sick leave days in employed asthma patients are around 23 days [6]. In Germany the total direct costs of asthma were measured to be about 2.35 billion euro; the costs for sick leave days caused by asthma were estimated to be 242 million euro for the year 2006 [7].…”
Section: Introductionmentioning
confidence: 99%
“…In industrialized countries, the costs of treatment AB reach 1-2% of total medical costs (Karmaus et al, 2013). However, is some countries can reach even up to 55% (Weissflog et al, 2001). Canadian study found 20.5% of const is attributable to inpatient care, 47.8% to outpatient care and 31.5% to medication (Sadatsafavi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Dies hat bereits die AIRE-Studie [3] mithilfe einer Befragung von 2803 Asthmapatienten dargestellt: Nur 5 % der Befragten wiesen eine vollständige Asthmakontrolle, wie in den GINA-Leitlinien definiert, auf [2]. Die Versorgung von Asthmapatienten in Deutschland ist vergleichbar unbefriedigend, wie mehrere Studien mithilfe von Arzneimittel-Routinedaten belegen [4][5][6][7][8][9]. Die Zahl der Publikationen aus Deutschland, die die Versorgung von Asthmapatienten in Deutschland thematisieren, ist gering [10].…”
Section: Abstract !unclassified
“…Die Zahl der Publikationen aus Deutschland, die die Versorgung von Asthmapatienten in Deutschland thematisieren, ist gering [10]. Weissflog et al [9] untersuchten die Kosten der Erkrankungen Asthma und chronische Bronchitis anhand von Sekundärdaten von Regierungsinstitutionen und pharmazeutischer Industrie. Größter Posten der direkten Kosten für Asthma bronchiale waren die ambulanten Arzneimittelkosten, gefolgt von den Kosten für Krankenhausaufenthalte.…”
Section: Abstract !unclassified